Implementation of Stunting Prevention Program Policy at Garut District Health Office - Yulia Agustina, Anisa; Rismayanti, Ema; Rustiana, Erna; Kania, Ikeu (Jurnal Polisci, 2023)
This study aims to examine how stunting prevention program policies are being implemented. An observational and interview-based strategy for data collecting is used in the study procedure. The findings indicated that four special intervention programs—one for adolescent girls, two for pregnant women, three for toddlers, and four for educational programs for adolescent girls, pregnant women, and families of toddlers—were used to implement the stunting prevention program policies. These programs used the following policy implementation concept approach from Van Metter and Van Horn: 1) Policy standards and objectives have been put into practice through the First 1000 Days of Life program; 2) socialization of suicide prevention programs to the community demonstrates communication; However, there are still many Posyandu cadres who need to improve their level of competence. 4) The characteristics of implementing agents are inseparable from the bureaucratic structure that carries out tasks under SOPs. 5) The implementer's attitude and the health workers involved have carried out their duties and functions correctly. 6) The social environment fully supports stunting prevention.